Phytochemical and Pharmacological Profile of Withania somnifera Dunal: A Review - Qamar Uddin, L. Samiulla, V. K. Singh, S. S. Jamil (Journal of Applied Pharmaceutical Science)
Withania somnifera (L) Dunal is a well known Indian medicinal plant widely used in the treatment of many clinical conditions in India. It is an important drug commonly known as Asgand which has been used either single or in combination with other drugs in Unani as well as Ayurvedic system of medicine for centuries. It has been described by Dioscorides (78 AD) in his book “Kitab-ul-Hashaish”. Asgand consists of the roots of Withania somnifera which has various therapeutic actions such as anti-inflammatory (Muhallil-e-Warm), sedative (Musakkin), alterative (Muaddil) and aphrodisiac (Muqawwi-e-Bah). Keeping in view the medicinal properties ofWithania somnifera Dunal (Asgand), an attempt has been made in this review paper to explore various dimensions of the drug including phytochemical and pharmacological studies carried out on this drug.
Keywords: Withania somnifera, Asgand, Anti-inflammatory activity, Immunomodulatory activity, Unani medicine.